Thai culture in the community in the case of conflict resolution in local administrative organizations - Noiwiang, Aoy (Thai Social Science Journal, 2025)
Thai culture is an important communication and connection tool between members of the local government society under the political structure that the community must govern itself. The important Thai culture that affects the cultural practices affects the local government structure, especially in the community development meeting at the sub-district administrative organization level where cultural practices interact with the behavior that the community must decide. The three important cultures are community, uncertainty avoidance, and power. They are also cultural practices that have a high influence on the community development meeting where cultural practices coat or envelop the truth to increase unity in the community to reduce conflict. The culture of saving face, respect, patronage leadership style, and openly displaying one’s own power is something that people in the countryside do not agree with. Most communities seem to be quite satisfied with the simple participatory model in the rural government structure. Communities have the possibility to influence the development of their villages through consultation in the local governance structure under Thai culture, even though they do not have the final decision-making power and the cultural values ​​may hinder their participation.